2013
DOI: 10.1016/j.athoracsur.2013.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Septal Dysfunction After Surgical Closure of Multiple Ventricular Septal Defects

Abstract: The postoperative ventricular global and septal functions were significantly reduced in children with multiple ventricular septal defects, especially in the cases with complex congenital heart disease and that were closed with large prosthetic materials. These results suggest that an effort to minimize the use of patch materials may lead to preserved postoperative ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Various imaging techniques have proven their value for intraoperative identification of the defects. Either cross‐sectional or three‐dimensional color Doppler echocardiography, including transesophageal imaging, and echocardiographic en‐face reconstruction of the right ventricular septal surface, have emerged as superior diagnostic modalities 1–72 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various imaging techniques have proven their value for intraoperative identification of the defects. Either cross‐sectional or three‐dimensional color Doppler echocardiography, including transesophageal imaging, and echocardiographic en‐face reconstruction of the right ventricular septal surface, have emerged as superior diagnostic modalities 1–72 …”
Section: Resultsmentioning
confidence: 99%
“…The causes of death were due to intractable pulmonary hypertensive crises, residual defects, and congestive cardiac failure. The requirement of reoperation for residual defects has been between 6% and 13%, with a reoperative mortality of around 33% 1–15,29–62 . The STS Congenital Heart Surgery Spring 2017 Database provides results from 116 participating centers on 7322 operations for ventricular septal defects over 4 years with mean operative mortality of 0.6%, mean cardiopulmonary bypass time of 77 min, and cross‐clamp time of 49 min 29–32 .…”
Section: Resultsmentioning
confidence: 99%
“…Because of all these considerations, some argue that the risks, in the long-term, are unacceptable, since they include apical dyskinesia, aneurysm formation, left ventricular dysfunction, ventricular arrhythmia, and the need for cardiac transplantation. 2,[30][31][32][57][58][59][60][61]65,66 The mechanisms identified that result in left ventricular dysfunction and aneurysm formation have included damage to epicardial coronary arteries, the myocardium, and the left ventricular conduction system. 11,58,60,61 It is also the case that the precise anatomic location and orientation of the ventriculotomy has great impact on the results.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][51][52][53][54][55] Orthotopic cardiac transplantation Cardiac transplantation has been recommended for extremely large apical septal defects with severe biventricular dysplasia, and persistent ventricular dysfunction following closure of Swiss-cheese septal defects through apical left ventriculotomy. 6,8,[29][30][31][32]41,42,47,[56][57][58][59][60]…”
Section: Hybrid Closure Of Multiple Apical Muscular Septal Defectsmentioning
confidence: 99%
See 1 more Smart Citation